Tailored PANI/Tio₂ Nanocomposites: Influence Of Tio₂ Loading On The Photocatalytic And Antimicrobial Behaviour (International Journal of Environmental Sciences, 2025)
PANI/TiO2 nanocomposite composites with different TiO2 weight percentages were synthesized by in-situ chemical oxidative polymerization method. Polymerization of aniline using ammonium persulfate (APS) in acidic medium at room temperature for the PANI/TiO2 nanocomposite. The nanocomposites were characterized by using PXRD, FTIR, UV-Vis, SEM and EDS. SEM images reveal that the samples exhibit a spherical morphology, with particle sizes for the various TiO2-loaded samples measured at 26 nm, 19 nm, 25 nm, and 24 nm, respectively. FTIR analysis shows the functional groups related to PANI and TiO2. Further the photocatalytic activity of nanocomposites was analysed for methylene blue dye. PANI/TiO2 nanocomposite photocatalystparticles come closer in the dye solution and agglomerate, thereby reducing thesurface-active sites of photocatalyst in contact with dye solution available forphotocatalytic reaction, Photocatalytic properties of PANI/TiO2were examined by degrading Reactive Black(MB) dye under visible light irradiation. PANI/TiO2(10%) showed the greatest degradation (92.46%). Due to synergistic effect between PANI and TiO2it is capable of absorbing visible light moreefficiently and decreasing the process of electron hole recombination. The nanocomposites also have significant antimicrobial activity against Streptococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa and Fungi Candida albicans, Aspergillus niger, Aspergillus Flavus.